The therapeutic efficacy of propranolol in children with recurrent primary epistaxis - Bjelakovic B; Bojanovic M; Lukic S; Saranac L; Vukomanovic V; Prijic S; Zivkovic N; Randjelovic D (Dove Medical Press, 2013)
Bojko Bjelakovic,1,2 Mila Bojanovic,2,3 Stevo Lukic,2,4 Ljiljana Saranac,1,2 Vladislav Vukomanovic,5,6 Sergej Prijic,5 Nikola Zivkovic,7 Dusica Randjelovic11Clinic of Pediatrics, Clinical Center, Nis, Serbia; 2Faculty of Medicine, University of Nis, Nis, Serbia; 3Clinic of Otorhinolaryngology, Clinical Center, Nis, Serbia; 4Clinic of Neurology, Clinical Center, Nis, Serbia; 5Mother and Child Health Institute, "Dr Vukan Cupic", Belgrade, Serbia; 6Faculty of Medicine, University of Belgrade, Serbia; 7Institute of Pathology, Faculty of Medicine, University of Nis, Nis, SerbiaAbstract: We hypothesized that some characteristics of beta-blockers, including negative inotropic, peripheral vasoconstrictor, and antiangiogenic effects, might be potentially useful in treating children with epistaxis. From June 2010 to March 2012, a total of seven children with recurrent primary epistaxis resistant to conventional management were observed at our institution. An overall effectiveness of propranolol was noted in all seven children when given a dose of 1.5–2 mg/kg/day (divided into three doses) as a second line therapy for terminating epistaxis. Based on our first experience, we believe that propranolol could be a favorable treatment option for patients with primary epistaxis.Keywords: beta-blocker, epistaxis, children